Is Religious Education Possible? : a Philosophical Investigation. - Hand, Michael (Continuum studies in research in education., 2006)
Is Religious Education Possible?: A Philosophical Investigation tackles a well-established problem in the philosophy of education. The problem is the threat posed to the logical possibility of non-confessional religious education by the claim that religion constitutes an autonomous language-game or form of knowledge. Defenders of this claim argue that religion cannot be understood from the outside: it is impossible to impart religious understanding unless one is also prepared to impart religious belief. Michael Hand argues for two central points: first, that non-confessional religious educat.